A Conceptual Shift in Studies of Belonging and the Politics of Belonging - Youkhana, Eva Shamiran (Social Inclusion, 2015)
The study of belonging, its underlying notions, and the politics of belonging shows that social, political, and territorial demarcations are still based on essentialist conceptions of the collective. These are often applied and reproduced in the social sciences as a result of methodological nationalism. Space-sensitive studies of migration and globalization and a return to the material have recently challenged social constructivist lines of argumentation and have provoked a conceptual shift from analytical categories with inherent spatiality, territoriality, and boundary marking to concepts based on movement and flow. In this paper the analysis of belonging and the related politics of belonging in migration studies incorporates space as an analytical category that cross-cuts established categorizations such as race, class, gender, and stage in the life cycle, and integrates a material semiotic perspective more systematically into the study of social relations at the intersection of the social categories mentioned. A new concept of belonging is defined which reflects the complex relations that individuals have with other people, circulating objects, artefacts, and changing social, political, and cultural landscapes, thus mirroring both the material conditions and the underlying power relations. Such an understanding of belonging proceeds from social naturalizations and fixations to the multiplicity and situatedness of individual attachments, which entangle social, imagined, and sensual-material relations that are constantly re-articulated and re-negotiated by actors in their day-to-day practices. In such a reading, belonging comes into being as a result of individual life stories, versatile contexts, and situated experiences and acts. In times of constant exchange through travel, mass media, and communication technologies, the conceptualization of belonging questions established sociocultural and political demarcations, indicates the compatibility of ascribed socio-cultural difference and stresses the permeability of borderlines. A space-sensitive theorization of social relations and belonging opens up new perspectives on the question of how social collectives are naturalized and by whom, and under which conditions they open up to new forms of belonging; it thus brings forth new findings about collectivization, social mobilization, and change.